2016
DOI: 10.1007/s11356-015-6027-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimating national-scale ground-level PM25 concentration in China using geographically weighted regression based on MODIS and MISR AOD

Abstract: Taking advantage of the continuous spatial coverage, satellite-derived aerosol optical depth (AOD) products have been widely used to assess the spatial and temporal characteristics of fine particulate matter (PM2.5) on the ground and their effects on human health. However, the national-scale ground-level PM2.5 estimation is still very limited because the lack of ground PM2.5 measurements to calibrate the model in China. In this study, a national-scale geographically weighted regression (GWR) model was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(41 citation statements)
references
References 43 publications
1
38
0
2
Order By: Relevance
“…The model obtained similar results to those obtained by the CTM used by van Donkelaar in 2010, but GWR found higher PM 2.5 concentrations in rural areas. Similar results for national PM 2.5 levels were found by You et al [126] with CV-R 2 values of 0.760 and 0.810 for MODIS and MISR, respectively, in China. Additionally, using 3-km resolution MODIS AOD in 2014, You et al [125] confirmed that this GWR approach is useful for estimating large-scale ground-level PM 2.5 distributions in China.…”
Section: Theory Background and Applicationsupporting
confidence: 88%
See 2 more Smart Citations
“…The model obtained similar results to those obtained by the CTM used by van Donkelaar in 2010, but GWR found higher PM 2.5 concentrations in rural areas. Similar results for national PM 2.5 levels were found by You et al [126] with CV-R 2 values of 0.760 and 0.810 for MODIS and MISR, respectively, in China. Additionally, using 3-km resolution MODIS AOD in 2014, You et al [125] confirmed that this GWR approach is useful for estimating large-scale ground-level PM 2.5 distributions in China.…”
Section: Theory Background and Applicationsupporting
confidence: 88%
“…(1) Model predictability: MLR was commonly used in early studies [17,20,21,[24][25][26][39][40][41]46,47,49,50,54,75], whereas MEM and CTM gradually became the dominant methods and replaced MLR after 2010. However, GWR has developed at a slower pace with a limited number of studies to data, and had moderate performance [32,74,125,126]. Included studies showed that R 2 value of MEM was higher than those of the other three models in the same area [17,87,104,136].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, quality assessment of MODIS AOD is crucial for local and global air quality applications. Studies have performed the quality assessment of the MODIS AOD [35,36,41,42,[47][48][49][50] and used it in statistical modeling based on the empirical linear regression, land use regression model, and Geo-graphically Weighted Regression (GWR) model for estimation of PM 2.5 concentrations at regional and global scales [14,[51][52][53][54][55][56][57][58][59][60][61][62][63][64]. These studies found that an accurate estimation of the PM 2.5 concentration depends on the quality of the satellite-retrieved AOD observations.…”
mentioning
confidence: 99%
“…We compare two geographically weighted regression (GWR) models that use MODIS AOD and WRF-Chem PM 2.5 with and without the "Percent of Facebook posters" dataset. GWR has previously been used in several different studies to predict surface air quality (Hu et al, 2013;Lassman et al, 2017;Song et al, 2014;You et al, 2016 each surface monitor location, which is then interpolated across the domain. We use the leave-one-out cross-validation (LOOCV) method to test our models, in which the regression coefficients determined at a single monitor are removed from the interpolation scheme.…”
Section: Regression Modelmentioning
confidence: 99%